Hubungan Antara Tingkat Pendidikan dan Kepuasan Pasien Terhadap Pelayanan Kefarmasiaan di UPT Puskesmas Kasongan: Correlation of Education Degrees and Customer Satisfaction for Pharmaceutical Care at UPT Puskesmas Kasongan - Mulia, Dewi Sari; Novaryatiin, Susi; Azkyannisa, Azizah (Jurnal Surya Medika (JSM), 2025)
Public awareness of health demands high-quality healthcare services. Satisfactory pharmaceutical care will foster patient loyalty and, over time, enhance the image of the Community Health Center (Puskesmas). Patient satisfaction is the result of the gap between expectations and the perceived characteristics of the service received. Education, both formal and non-formal, plays an important role in shaping individuals’ ways of thinking, behavior, and attitudes, which ultimately contribute to the collective awareness of the community. Therefore, the purpose of this study is to determine whether there is a relationship between the level of education and patient satisfaction based on the five (5) dimensions of service quality. The method used in this research is descriptive-analytic with a quantitative approach. Based on the research results analyzed using SPSS and the Somers’ D bivariate correlation test, it showed that a weak correlation was only found in the empathy dimension with a    p-value of 0.431 and a correlation coefficient of 0.104. Thus, it can be concluded that there is no significant relationship between the level of education and patient satisfaction with pharmaceutical services at UPT Puskesmas Kasongan.